Соціально-економічні аспекти структурної трансформації економіки України - Подзізей, Владислав Володимирович; Шматковська, Тетяна Олександрівна (My University, 2024)
У статті розглянуто соціально-економічні аспекти структурної трансформації економіки України в контексті сучасних викликів та можливостей. Визначено ключові напрямки її реформування, орієнтовані на загальне зміцнення конкурентоспроможності та забезпечення сталого розвитку економіки країни. Досліджено вплив структурних змін на соціальну сферу, зокрема на зайнятість, рівень життя населення та соціальну диферен-ціацію. Проаналізовано результати реформ бюджетної децентралізації та місцевого самоврядування, а також ідентифіковано проблемні аспекти, котрі потребують подальшого вирішення. Розглянуто вплив структурної трансформації на інвестиційний клімат та розвиток малих та середніх підприємств в аспекті його впливу на соціально-економічний розвиток країни. Доведено необхідність формування підходів щодо подолання про-блем, які виникають у процесі структурних змін в контексті перспектив відновлення та подальшого розвитку національної економіки України.
The purpose of the article is to study the socio-economic aspects of the structural transformation of the economy of Ukraine, their impact on employment, the standard of living of the population and other aspects of the social sphere in order to determine the prospects for the further development of the national economy in the context of the reforms. The relevance of the research topic is determined by the need to improve the economic system of Ukraine in the conditions of war and constant challenges to its stability and competitiveness. The research uses a complex methodological approach, which includes the analysis of empirical data, comparative analysis of information and the use of theoretical models of socio-economic processes. The impact of structural changes on such key indicators as employment, the standard of living of the population, social differentiation, the investment climate and the development of small and medium-sized enterprises is analyzed. Successes achieved and problematic aspects that require further attention and resolution are identified. Special attention is paid to the development of recommendations for improving the efficiency of economic policies and strategies of state administration in order to promote sustainable development and increase the welfare of the population. The article examines the socio-economic aspects of the structural transformation of the Ukrainian economy in the context of modern challenges and opportunities. The key areas of its reform are determined, focused on general strengthening of competitiveness and ensuring sustainable development of the country's economy. The impact of structural changes on the social sphere, in particular on employment, the standard of living of the population and social differentiation, was studied. The results of the budget decentralization and local self-government reforms were analyzed, as well as problematic aspects that require further resolution were identified. The impact of structural transformation on the investment climate and the development of small and medium-sized enterprises in terms of its impact on the socio-economic development of the country is considered.
Keywords: структурна трансформація економіки; соціально-економічний розвиток; соціальна сфера; зайнятість; рівень життя населення; 330.341.4